« Une femme en Côte d’Ivoire, une femme au Burkina Faso » - François Ruf (EchoGéo)
Côte d’Ivoire, with its diversity of forest and savannah regions, and its neighbour to the north, Burkina Faso, are historically linked to the creation and growth of the Ivorian village plantation economy based on the ‘coffee-cocoa’ pairing. The land of the former has always needed the workforce of the latter. This combination of land and labour was made possible with little capital and without any involvement of capitalists in production. Families from Côte d’Ivoire and Burkina Faso, mainly migrants, remain the backbone of the cocoa sector. Within the family, strategies evolve through networks, across several economic spaces. Women’s contribution to labour on cocoa farms and adjacent fields of food crops is known and acknowledged. But what could be the importance and role of the farmers’ wives who remain behind in – or later return to – the ‘home country’ and the ‘home village’? This question, apparently little studied, is addressed through surveys in the cocoa migration villages in Côte d’Ivoire, i.e., of growers and husbands who speak about their wives back in the home villages, supplemented with information gathered from co-wives who stay with their husbands. A sample of 209 migrant farmers, including 117 who claim to be of Burkinabe origin, is spread over a dozen villages on either side of the Sassandra River. A first result is the frequency of the phenomenon, involving up to 20% of migrant households. The reason behind these women’s continued residence in their villages of origin can be found in strategies that combine the objectives of solidarity and family security, education, and maintenance of networks. But these women ‘back in the village’ are also motivated by substantial and diversified investments, the structural determinants around cocoa cultivation, and policy: declining cocoa prices since 1988, falling yields from ageing cocoa farms, political and military crises, and new land-related issues . These profound ecological, economic, and political changes of the 2000s generate or accelerate the process of ‘return’ of wives to the home village – and the spectacular boom of cashew cultivation in Côte d’Ivoire, in which women play an important role, for example in the groups claiming an Abron/Koulango origin, along the Ghanaian border. Their ‘return’ to the village of origin can be interpreted as a post-cocoa migration, and a driver of diversification and investment. These ‘women who stay back or return’ not only reflect history, the stakes and issues of the Ivorian – or rather ‘Ivorian/West African’ – plantation economy, but also themselves write a new page in it.